PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN GEOGEBRA DAN MICROSOFT MATHEMATIC DI LA ROYBA ISLAMIC SCHOOL - Cynthia Rahmawati (Fakultas Ilmu Komputer dan Desain - Unsurya, 2019)
One of the learning media that suits the current development especially in learning in the field of mathematics is the use of software. Usefulness of software can help teachers to deliver abstract mathematical material becomes more easily understood because the software can visualize learning in that field. In addition, Geogebra and Microsoft Mathematic are designed to train the ability independently in the creativity and critical power of students. This study aims to develop learning media through software Geogebra and Microsoft Mathematic on junior high and high school materials at La Royba Islamic School. The results obtained are GeoGebra and Microsoft Math can be used as a medium of learning in math and can be downloaded for free, so it is easy to get it. Based on the research also, the student activity using the geogebra software and Microsoft math experienced a change toward a better attitude. This change starts from the student's attitude enough, good enough, and good to the development of learning media of mathematics using geogebra and Microsoft math. In addition, with the features and ease of existing applications in both this software can help teachers in delivering learning materials, so that students can be actively involved independently and make learning more creative, effective and meaningful. Creativity is honed to students may also increase the creativity of students with an understanding that can create their own mathematical problem solving in accordance with the wishes of students. Both of these software have special benefits with GeoGebra emphasizes on Geometry while Microsoft Math on Algebra or linear equations. Based on all this, it can be concluded that Geogebra and microsofth mathematic is feasible and can be used as a medium of learning.